WDPCP Modulates Cilia Beating Through the MAPK/ERK Pathway in Chronic Rhinosinusitis With Nasal Polyps - Ma, Yun; Tian, Peng; Zhong, Hua; Wu, Fan; Zhang, Qining; Liu, Xiang; Dang, Hua; Chen, Qiujian; Zou, Hua; Zheng, Yiqing (Frontiers in Cell and Developmental Biology, 2021)
Cilia loss and dysfunction is one of the typical pathological features of chronic rhinosinusitis with nasal polyps (CRSwNP). Tryptophan-aspartic acid (W-D) repeat containing planar cell polarity effector (WDPCP) has been proven to be an essential element for ciliogenesis in human nasal epithelium, but its role in the beating of cilia remains unclear. In this study, we sought to investigate the role of WDPCP and its underlying mechanism behind the dysfunction in the beating of cilia in nasal polyp tissue. We demonstrated WDPCP expression in the epithelium of nasal polyps. We also investigated the MAPK/ERK pathway in primary human sinonasal epithelial cells to explore the function of WDPCP. The air-liquid interface culture system was used as a model to verify the role of WDPCP and the MAPK/ERK pathway in the beating of cilia. With the dysfunction of cilia beating, we observed a low expression of WDPCP in the epithelium of nasal polyp tissues. Within the in vitro study, we found that WDPCP was critical for mitochondrial biogenesis and mitochondrial function in human sinonasal epithelial cells, possibly due to the activation of the MAPK/ERK pathway. The mitochondrial dysfunction caused by U0126 or lacking WDPCP could be partially recovered by dexamethasone. The low expression of WDPCP in nasal epithelium could affect mitochondria via the MAPK/ERK pathway, which may contribute to the dysfunction in the beating of cilia in CRSwNP.